Etnomatematika Kota Bengkulu: Eksplorasi Makanan Khas Kota Bengkulu Bay Tat untuk Memahami Pembelajaran Matematika Di Sekolah - Yuni Pusvita; Herawati Herawati; Wahyu Widada (Jurnal Pendidikan Matematika Raflesia, 2019)
Ethnomatematics is mathematics in a culture. The culture in question is the habits of human behavior in the environment, such as the behavior of urban or rural community groups, work groups, professional classes, students in age groups, indigenous communities, and certain other groups. Various attempts have been made to foster enthusiasm and student motivation towards mathematics. For example improvements in the curriculum, methods, and learning models applied. With the hope of improving student learning outcomes and abilities. One such effort is through ethnomatematics-based learning. Ethnomatematics-based mathematics learning has proven to be effective in improving students' mathematical understanding abilities. It is proven that from the results of research and several indicators of students 'understanding ability states that there is an influence of ethnomatematics on students' mathematical understanding abilities, namely in terms of identifying, translating, interpreting symbolic meanings, understanding and applying mathematical ideas, making an exploration (estimation) and the increasing value of student learning outcomes.